Assessment of Plasmodium falciparum anti-malarial drug resistance markers in pfk13-propeller, pfcrt and pfmdr1 genes in isolates from treatment failure patients in Democratic Republic of Congo, 2018–2019 - Yobi, Doudou M. (Malar J, 2021)
BACKGROUND: The national policy for malaria treatment of the Democratic Republic of Congo recommends two first-line artemisinin-based combinations for the treatment of uncomplicated malaria: artesunate-amodiaquine and artemether-lumefantrine. This study investigated the presence of markers associated with resistance to the current first-line artemisinin-based combination therapy (ACT) in isolates of Plasmodium falciparum from treatment failure patients in the Democratic Republic of Congo. METHODS: From November 2018 to November 2019, dried blood spots were taken from patients returning to health centres for fever within 28 days after an initial malaria treatment in six sentinel sites of the National Malaria Control Programme across Democratic Republic of Congo. The new episode of malaria was first detected by a rapid diagnostic test and then confirmed by a real-time PCR assay to define treatment failure. Fragments of interest in pfk13 and pfcrt genes were amplified by conventional PCR before sequencing and the Pfmdr1 gene copy number was determined by a TaqMan real-time PCR assay. RESULTS: Out of 474 enrolled patients, 364 (76.8%) were confirmed positive by PCR for a new episode of P. falciparum malaria, thus considered as treatment failure. Of the 325 P. falciparum isolates obtained from 364 P. falciparum-positive patients and successfully sequenced in the pfk13-propeller gene, 7 (2.2%) isolates carried non-synonymous mutations, among which 3 have been previously reported (N498I, N554K and A557S) and 4 had not yet been reported (F506L, E507V, D516E and G538S). Of the 335 isolates successfully sequenced in the pfcrt gene, 139 (41.5%) harboured the K76T mutation known to be associated with chloroquine resistance. The SVMNT haplotype associated with resistance to amodiaquine was not found. None of the isolates carried an increased copy number of the pfmdr1 gene among the 322 P. falciparum isolates successfully analysed. CONCLUSION: No molecular markers currently known to be associated with resistance to the first-line ACT in use were detected in isolates of P. falciparum from treatment failure patients. Regular monitoring through in vivo drug efficacy and molecular studies must continue to ensure the effectiveness of malaria treatment in Democratic Republic of Congo.